Konsep Etika Dalam Perspektif Ta’dib Syed Muhammad Naquib Al-Attas - Jamil, Muhammad Shobrun; Fadhilah, Fahreza Ahmad (Halaqa: Journal of Islamic Education, 2025)
The moral crisis and value disorientation plaguing modern education is one of the fundamental issues of the contemporary era. This study discusses the concept of ethics from the perspective of ta'dīb as formulated by Syed Muhammad Naquib al-Attas as the basic framework of Islamic education. This study uses a qualitative design. The approach used is descriptive-analytical and the method employed is library research, as all data were obtained from written sources, including al-Attas's original works and secondary studies discussing his ideas. Based on the research findings, the concept of ta'dīb is not merely an effort to impart knowledge but also a process of forming adab, which involves placing things in their proper places, culminating in the recognition and acknowledgment of divine truth. Ethics in ta'dīb is not separate from knowledge and morality but is an integral integration of all three. This study also examines Al-Attas' critique of the modern Western educational paradigm, which is deemed secular, dualistic, and incapable of addressing contemporary moral crises. Through a qualitative-philosophical approach and literature review, this paper asserts that ta'dīb serves as an ethical alternative in education deeply rooted in the Islamic worldview.